Work Climate and Organisational Politics as Predictors of Organisational Commitment among Staff of Benue State University, Makurdi - Ogwuche, Chinelo Helen; Suleiman, Umar Aliyu; Onah, Caleb (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigated work climate and organisational politics as predictors of organisational commitment among employees of Benue State University, Makurdi. Employing an ex-post facto research design, three hypotheses were formulated, and a sample of 187 participants completed the Organisational Climate Questionnaire (OCQ), Perceived Organisational Politics Scale (POPS), and Organisational Commitment Questionnaire (OCQ). Data analysis involved regression and multiple regression techniques. Hypothesis one, positing that work climate significantly influences organisational commitment among Benue State University staff, was supported (R =.185, R2 =.034, F(1,177) = 6.229, P <.05). Hypothesis two, which suggested that organisational politics significantly affects organisational commitment, was also supported (R =.629, R2 =.396, F(1,181) = 117.960, P <.05). Additionally, Hypothesis three, indicating a joint influence of work climate and organisational politics on organisational commitment, was affirmed (R =.632, R2 =.400, F(2,173) = 56.950, P <.001). Recommendations derived from the findings include prioritising employees commitment to enhance productivity, mitigating favouritism within the organisation to facilitate effective task execution, and empowering managers to assess and improve work climate, thereby fostering a motivating environment conducive to ongoing performance enhancement.